Poor prognostic implications of myelodysplasia-related mutations in both older and younger patients with de novo AML - Xavier Cheng-Hong Tsai; Kuo-Jui Sun; Min-Yen Lo; Feng-Ming Tien; Yuan-Yeh Kuo; Mei-Hsuan Tseng; Yen-Ling Peng; Yi-Kuang Chuang; Bor-Sheng Ko; Jih-Luh Tang; Hsun-I Sun; Ming-Chih Liu; et al. (Blood Cancer Journal, 2023)
Abstract A set of myelodysplasia-related (MDS-R) gene mutations are incorporated into the 2022 European LeukemiaNet risk classification as adverse genetic factors for acute myeloid leukemia (AML) based on their poor prognostic impact on older patients. The impact of these mutations on younger patients (age < 60 years) remains elusive. In the study of 1213 patients with de novo non-M3 AML, we identified MDS-R mutations in 32.7% of the total cohort, 44.9% of older patients and 23.4% of younger patients. The patients with MDS-R mutations had a significantly lower complete remission rate in both younger and older age groups. With a median follow-up of 9.2 years, the MDS-R group experienced shorter overall survival (P = 0.034 for older and 0.035 for younger patients) and event-free survival (P = 0.004 for older and 0.042 for younger patients). Furthermore, patients with MDS-R mutations more frequently harbored measurable residual disease that was detectable using next generation sequencing at morphological CR than those without MDS-R mutations. Allogeneic hematopoietic stem cell transplantation (allo-HSCT) might ameliorate the negative impact of MDS-R mutations. In summary, AML patients with MDS-R mutations have significantly poorer outcomes regardless of age. More intensive treatment, such as allo-HSCT and/or novel therapies, is warranted for AML patients with MDS-R mutations.